The Effect of Katuk Leaf Decoction on Breast Milk Production Among Postpartum Mothers - Anggraini, Anggraini; Ermasari, Anissa; Sunarsih, Sunarsih; Yunani, Risa; Rochmawati, Rochmawati (MEDICA (International Medical Scientific Journal), 2026)
Insufficient breast milk production remains a major barrier to achieving exclusive breastfeeding at both global and national levels. In Indonesia, exclusive breastfeeding coverage declined from 88.9% in 2021 to 82.2% in 2023. The use of plant-based herbal galactagogues, particularly Sauropus androgynus (katuk leaves), is widely practiced; however, comparative evidence against active interventions such as lactation education remains limited. This study aimed to compare the effectiveness of katuk leaf decoction and breastfeeding technique education in increasing breast milk production among postpartum mothers. A quantitative study with a quasi-experimental pretest–posttest control group design was conducted involving 32 postpartum mothers selected through purposive sampling from a population of 66, comprising 16 respondents in the intervention group (katuk leaf decoction 150 ml/day for 7 days) and 16 respondents in the control group (breastfeeding technique education). Breast milk production was assessed using a structured observation sheet based on four proxy indicators. Data were analyzed using the Wilcoxon signed-rank test for within-group comparisons and the Mann–Whitney test for between-group comparisons. The results showed that breast milk production scores increased in both groups, with a higher mean increase observed in the intervention group (from 4.44 to 6.56; Δ=2.12) compared with the control group (from 4.19 to 5.94; Δ=1.75). Within-group analysis demonstrated statistically significant improvements in both groups (p=0.001), and between-group comparison revealed a statistically significant difference in score changes (p<0.05). In conclusion, katuk leaf decoction demonstrated a greater increase in breast milk production compared with breastfeeding technique education; however, these findings should be interpreted cautiously due to methodological limitations, and further studies using more rigorous designs are recommended.